Regulatory Challenges of Airport Slot Allocation in the European Union - Kociubiński, Jakub (University of Wroclaw. Faculty of Law, Administration & Economics, 2013)
The airport capacity of every airport is measured by the number of slots, which means the right to use runway at a specified time, on a specified day. This capacity is limited and for many reasons inelastic, while demand is constantly rising, creating bottlenecks for air traffic. As the problem of congestion worsens, as are the inevitable service delays accompanied by losses for operators and the economy as a whole, regulators, airports management and other stakeholders have become increasingly concerned with the issue of how to fairly and efficiently distribute these scarce resources.In order to create and sustain an efficient and non-discriminatory system of slot rationing a few crucial questions must be answered. Should slots be allocated by monetary exchanges or be allotted freely? Who should be responsible for this allocation? Who should have the first claim for available slots? On the eve of reform of the European Union’s slot distribution system it is also vital to explore various alternatives based on experience gained under the current system and its shortcomings. This paper will attempt to tackle these issues.
Keywords: Unia Europejska; sloty; prawo do korzystania z pasa startowego; przepustowość